Hematologic disorders in liver failure: pathophysiology and therapeutic considerations - Hernández Ángeles, Yossadara (2024)
Alterations in blood cell counts are the most prominent and recurrent clinical findings among patients suffering from both acute and chronic liver disease. These changes are an important marker of liver failure and often play a key role in the evaluation and management of these patients. Together with the prolongation of coagulation tests, thrombocytopenia is the most common disorder among these individuals. This condition, as well as leukopenia, is largely attributable to hypersplenism, a disorder in which the spleen retains and destroys blood cells, including platelets. However, when the platelet count drops below 10x103/µl, it is essential to consider other causes, such as autoimmune factors that may be contributing to the development of thrombocytopenia. Anemia, defined as a decrease in red blood cell count or hemoglobin levels, is another common characteristic of liver disease. Although in most cases macrocytic anemia occurs, in some situations it can be secondary to hemolytic events, as observed in Zieve’s syndrome. This wide range of manifestations of anemia among liver patients highlights the complex interaction between liver and blood components. Despite advances in understanding the underlying causes of these cytopenias, treatment options remain limited. Therapeutic options generally focus on the transfusion of blood products to compensate for deficiencies in cell counts or on the use of thrombopoietin (TPO) analogues to temporarily stimulate platelet production in the bone marrow. However, these treatments tend to address the symptoms rather than the root causes of hematologic disorders in liver disease. The persistence and worsening of these disorders may serve as early indicators of the progression of liver failure. The complicated relationship between liver and hematological homeostasis remains the subject of research. A deeper understanding of these mechanisms could potentially open the door toward more targeted and effective therapeutic approaches to address cytopenias in the context of liver disease.